Establishment and functioning of the savanna marshes of the Lopé National Park in Gabon since the termination of the African humid period and the arrival of humans 2500 years ago. (July 2021) - Bremond, Laurent; Oslisly, Richard; Sebag, David; Bentaleb, Ilham; Favier, Charly; Henga-Botsikabobe, Karl; Mvoubou, Makaya; Ngomanda, Alfred; de Saulieu, Geoffroy; ,
Holocene paleoecological studies in tropical Africa are rare because most lakes either dried out at the termination of the African Humid Period or have since filled up. However, tropical sedge marshes can be an alternative to perform long-term ecological studies. The Lopé National Park (LNP) in Gabon is a mosaic of forest and savanna enclosed in the equatorial forest, where open areas facilitated the development of peat marshes accumulating several-meter-thick sediment. In order to reconstruct the historical dynamic in these marshes through a local and regional point of view, we compared sedimentological, continuous X-ray fluorescence, and stable isotopic analyses on sediment cores from six herbaceous marshes in the LNP. A reliable chronological frame was based on 50 14 C dates, over the last 2500 years in most sites, and reaching 9000 years in one marsh. We show that the origin of these marshes is a major hydrological change, 3450 and 2300 years ago, that affected the entire region, almost concomitantly with the diffusion of Iron Age population. The sedimentation within marshes is homogenous with low intra-site variability. In contrast, high inter-sites variability evidences that the functioning of the marsh itself exerts a much more significant influence than in lakes. However, a regional event is recorded between 1400 and 800 years ago, concurrently with an archeological trace hiatus throughout the forest hinterland of West Central Africa.